Structural and Functional Genomics of the Resistance of Cacao to Phytophthora palmivora - Jonathan Javier Mucherino Muñoz; Cláusio Antônio Ferreira de Melo; Raner José Santana Silva; Edna Dora Martins Newman Luz; Ronan Xavier Corrêa (Pathogens, 2021)
Black pod disease, caused by Phytophthora spp., is one of the main diseases that attack cocoa plantations. This study validated, by association mapping, 29 SSR molecular markers flanking to QTL (Quantitative Trait Loci) associated with Phytophthora palmivora Butler (Butler) (PP) resistance, in three local ancient varieties of the Bahia (Comum, Pará, and Maranhão), varieties that have a high potential in the production of gourmet chocolate. Four SSR loci associated with resistance to PP were detected, two on chromosome 8, explaining 7.43% and 3.72% of the Phenotypic Variation (%PV), one on chromosome 2 explaining 2.71%PV and one on chromosome 3 explaining 1.93%PV. A functional domains-based annotation was carried out, in two Theobroma cacao (CRIOLLO and MATINA) reference genomes, of 20 QTL regions associated with cocoa resistance to the pathogen. It was identified 164 (genome CRIOLLO) and 160 (genome MATINA) candidate genes, hypothetically involved in the recognition and activation of responses in the interaction with the pathogen. Genomic regions rich in genes with Coiled-coils (CC), nucleotide binding sites (NBS) and Leucine-rich repeat (LRR) domains were identified on chromosomes 1, 3, 6, 8, and 10, likewise, regions rich in Receptor-like Kinase domain (RLK) and Ginkbilobin2 (GNK2) domains were identified in chromosomes 4 and 6.